ANALISIS SPEED, AGILITY, POWER, DAN VO2 MAX PADA EKSTRAKURIKULER FUTSAL SMP NEGERI 2 MADIUN - Wiriawan, Oce; Sukmanda, Taufan Fajar (Journal of Sport Science and Education, 2017)
Futsal is the most popular sport around the world including Indonesia. This is shown from the enthusiasm of Indonesian people who love this futsal sport, and make this sport growing rapidly in Indonesia so many community standing futsal or futsal club in Indonesia. Futsal is indoor soccer game or open space. Each team has 5 members. Futsal is very welcome by the wider community, especially in Indonesia. In addition, many futsal matches are held in these areas. Compared with other sports, futsal is very popular and is not inferior to football and other sports.The purpose of this research is to find the empirical answer from the problems that have been formulated, namely (1) To know what is the speed skill of soccer player futsal SMP Negeri 2Madiun (2) To know what is the ability of the soccer player in SMP Negeri 2 Madiun (3) To know what is the ability of agility players in SMP Negeri 2 Madiun and (4) to know the ability of Vo2Max players futsal SMP Negeri 2 Madiun.This research method is quantitative. While the approach used in this studyIs a descriptive approach. The target of the research is the students who follow the extracurricular sport futsal. Technique of collecting data using weight test, running 30 meter, shuttel run test, vertical jump test, and Bleep test, test used to know the result of quantitative data analysis of Speed, Agility, Power, and Vo2Max to extracurricular sport futsal SMP Negeri 2 Madiun .The result of the research shows that Speed of futsal sport of SMP Negeri 2 Madiun is categorized as Good. The percentages are: (40%) excellent category, (35%) good category, (10%) medium category, (10%) less category, and (10%) less category once. Percentage Agility of futsal sport SMP Negeri 2 Madiun is categorized less. With the percentage are: (10%) very good category, (35%) good category, (15%) medium category (35%) category less (5%) category less once. Percentage of Power of soccer futsal SMP Negeri 2 Madiun is categorized very less. The percentages are: (20%) excellent category, (20%) good category, (25%) medium category (25%) category less (10%) less category once, and VO2max percentage of sport futsal SMP Negeri 2 Madiun is categorized very less . The percentages are: (10%) excellent category, (15%) good category, (40%) medium category (30%) less category (5%) less category once. Thus, the results of Speed, Agility, Power and VO2Max tests in SMP Negeri 2 madiunmasih are very less under the target thus can be used as study and as input for the Extracurricular Training Coach of Futsal Branch SMP Negeri 2 Madiun. To improve the ability, especially Agility, Power, and VO2 Max which is very useful for students in the game that matches the needs of each Extracurricular Futsal Sports Branch as well as selection of players is necessary and paid attention to the trainer to improve the quality and achievement in the future.